Reversing Platinum Resistance in High-Grade Serous Ovarian Carcinoma: Targeting BRCA and the Homologous Recombination System - Wiedemeyer, Wolf Ruprecht; Beach, Jessica A.; Karlan, Beth Y. (Frontiers in Oncology, 2014)
Resistance to platinum chemotherapy is one of the main factors driving ovarian cancer mortality, and overcoming platinum resistance is considered one of the greatest challenges in ovarian cancer research. Genetic and functional evidence points to the homologous recombination (HR) DNA repair system, and BRCA1 and BRCA2 in particular, as main determinants of response to platinum therapy. BRCA-mutant ovarian cancers are especially sensitive to platinum, associated with better survival, and amenable to PARP inhibitor treatment. Here, we discuss a therapeutic concept that seeks to disrupt HR capacity via targeting of BRCA1 and BRCA2 functionality in order to reverse platinum resistance in BRCA-proficient high grade serous ovarian cancers (HGSOCs). We review the molecular signaling pathways that converge on BRCA1 and BRCA2, their activation status in ovarian cancer, and therapeutic options to modulate BRCA function. Several recent publications demonstrate efficient chemosensitization of BRCA-proficient cancers by combining targeted therapy with standard platinum-based agents. Due to its inherent genomic heterogeneity, molecularly defined subgroups of HGSOC may require different approaches. We seek to provide an overview of available agents and their potential use to reverse platinum resistance by inhibiting the HR system, either directly or indirectly, by targeting oncogenic activators of HR.